Molecular Identification, Antifungal Susceptibility, and Geographic Origin of Clinical Strains of Sporothrix schenckii Complex in Mexico - Rojas, Olga; Bonifaz, Alexandro; Campos, Christian; Treviño Rangel, Rogelio de Jesús; González Álvarez, Rafael; González González, Gloria María (2018)
Abstract:SporotrichosisisasubcutaneousmycosiscausedbySporothrixschenckiicomplex. Thedisease asbeenreportedworldwide.However,theincidenceoftheetiologicalagentvariesinitsgeographic distribution. We studied 39 clinical isolates of Sporothrix schenckii from diverse regions in Mexico, collectedfrom1998to2016.Molecularidentiﬁcationwasperformedbysequenceanalysisofthepartial calmodulin gene. In vitro antifungal susceptibility to amphotericin B (AMB), itraconazole (ITC), voriconazole (VRC), posaconazole (PSC), ﬂuconazole (FLC), terbinaﬁne (TRB), caspofungin (CSF), anidulafungin (ANF), and micafungin (MCF) was evaluated. Thirty-eight isolates of S. schenckii complexweredividedintoﬁvesupportedcladesinaphylogenetictree. Thepredominantclinicalform waslymphocutaneous(92.3%),ﬁxedcutaneous(5.1%),anddisseminated(2.5%). Terbinaﬁneexhibited the best in vitro antifungal activity, while ﬂuconazole was ineffective against Sporothrix schenckii complex. Our results showed diverse geographic distribution of clinical isolates in eight states; deﬁnitive identiﬁcation was done by CAL gen PCR-sequencing. In Mexico, S. schenckii is considered to be an etiological agent of human sporotrichosis cases, and lymphocutaneous is the most prevalent form of the disease. This study revealed four clades of S. schenckii sensu stricto by phylogenetic analysis. Furthermore, we report one case of S. globosa isolated from human origin from the North of Mexico.